Very high cycle fatigue of TC4 titanium alloy under variable stress ratio: Failure mechanism and life prediction. (November 2017) - Li, Wei; Zhao, Hongqiao; Nehila, Abdelhak; Zhang, Zhenyu; Sakai, Tatsuo
Graphical abstract: (a) Duplex S–N curves associated with surface and interior failures under R = −0.3, 0.1, 0.3 and 0.5, and only related to surface failure under R = −1; (b) Surface crack nucleation area; (c) Facets with slip lines at the surface crack nucleation area for R > 0; (d) Interior failure associated with GBF and fisheye in the VHCF regime; (e) Facets with slip lines at the GBF area. Highlights: The interior failure mechanism involving facets → GBF → fish-eye → final failure was elucidated. An energy-based crack nucleation life model associated with failure mechanism was established. A VHCF life prediction approach involving crack nucleation and growth behavior was developed. Abstract: Axial loading tests with variable stress ratio were performed to investigate the very high cycle fatigue property of TC4 titanium alloy, and a life prediction approach associated with failure mechanism was proposed. The interior failure process is characterized as: (1) occurrence of slip lines or bands on partial α grains, (2) nucleation of micro-cracks within some α grains, (3) coalescence of micro-cracks and formation of granular bright facets, (4) stable macro-crack growth within fisheye (5) unstable crack growth outside fisheye and (6) momentary fracture. The validity of approach is confirmed by the good agreement between predicted and experimental results.